Ethylene Carbonate and Polyethylene Glycol as Efficient Plasticizers in CMC-PVA-NH4NO3-Based Polymer Electrolyte - Mohd Ali, Noor Saadiah; Nagao, Yuki; Samsudin, Ahmad Salihin (Makara Journal of Technology, 2020)
This study investigated the influence of plasticizers (polyethylene glycol [PEG] and ethylene carbonate [EC]) on the ionic conduction of CMC-PVA-NH4NO3. Blended biopolymer electrolytes (BBEs) based on carboxymethyl cellulose–polyvinyl alcohol (CMC-PVA) doped with ammonium nitrate (NH4NO3) were obtained via casting solution technique incorporated with PEG and EC, which acted as plasticizers. Electrical impedance spectroscopy (EIS) was conducted to evaluate the effect of plasticization on the ionic conduction properties. The ionic conductivity improved from 1.70 × 10−3 S/cm for un-plasticized BBEs to 3.92 × 10−3 S/cm for plasticized BBEs with EC and 3.00 × 10−3 S/cm for plasticized BBEs with PEG. The improvement indicated that the plasticizers weakened the Coulombic force and promoted further dissociation in the ionic dopant. The highest ionic conductivity was achieved for BBEs plasticized with EC, thereby suggesting the suitability of EC as plasticizer in this present system. The BBE system showed the Arrhenius characteristic at elevated temperatures and demonstrated increasing ionic conductivity. Dielectric properties of all BBE systems were found to improve upon the addition of EC and PEG, demonstrating their correlation with ionic conductivity.